2020
DOI: 10.1111/gcb.15266
|View full text |Cite
|
Sign up to set email alerts
|

Climatic breadth of calling behaviour in two widespread Neotropical frogs: Insights from humidity extremes

Abstract: Climate change is severely altering precipitation regimes at local and global scales, yet the capacity of species to cope with these changes has been insufficiently examined. Amphibians are globally endangered and particularly sensitive to moisture conditions. For mating, most amphibian species rely on calling behaviour, which is a key weather‐dependent trait. Using passive acoustics, we monitored the calling behaviour of two widespread Neotropical frogs in 12 populations located at the humidity extremes but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 112 publications
(189 reference statements)
0
3
0
Order By: Relevance
“…cold vs. warm extremes; dry vs. wet extremes, or sites with distinct multi‐dimensional parameters identified with a clustering approach), hence covering most of the range of climatic variation experienced by the study species to approach the environmental breadth of their calling behaviour. It has been demonstrated that examining the performance of the study species at contrasting climatic conditions can contribute substantially to assess the influence of climate on calling behaviour, even when monitoring only two populations (Bonnefond et al, 2020; Llusia, Márquez, Beltrán, Benítez, et al, 2013; Llusia, Márquez, Beltrán, Moreira, et al, 2013).…”
Section: Acoustic Species Distribution Models: Methodological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…cold vs. warm extremes; dry vs. wet extremes, or sites with distinct multi‐dimensional parameters identified with a clustering approach), hence covering most of the range of climatic variation experienced by the study species to approach the environmental breadth of their calling behaviour. It has been demonstrated that examining the performance of the study species at contrasting climatic conditions can contribute substantially to assess the influence of climate on calling behaviour, even when monitoring only two populations (Bonnefond et al, 2020; Llusia, Márquez, Beltrán, Benítez, et al, 2013; Llusia, Márquez, Beltrán, Moreira, et al, 2013).…”
Section: Acoustic Species Distribution Models: Methodological Frameworkmentioning
confidence: 99%
“…In combination with niche modelling, these novel techniques may assist researchers in providing a basis for the development of new species distribution models: aSDMs. Recent studies have shown how acoustic monitoring can be used to estimate climatic breadth and environmental suitability for calling behaviour (Bonnefond et al, 2020; Llusia, Márquez, Beltrán, Benítez, et al, 2013), laying the foundations for aSDMs. These estimates constitute a novel source, not only of eco‐physiological information to model species distribution, but also behavioural and phenological information, improving our tools to predict past, present and future environmental suitability for vocal animals.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these fields have adopted other methods. While there has been at least one study highlighting the issues with the STFT spectrogram in the study of animal sounds (Brumm et al., 2017 ), this remains the most common method in the biological sciences (Baotic et al., 2014 ; Benko & Perc, 2009 ; Bonnefond et al., 2020 ; Bussmann et al., 2021 ; Cazau et al., 2016 ; Davenport et al., 2022 ; Dutour et al., 2021 ; Forti et al., 2017 ; Gonzalo‐Tarodo et al., 2020 ; Jégh‐Czinege et al., 2020 ; Leroy et al., 2021 ; Malige et al., 2020 ; Mann et al., 2021 ; Maruska & Mensinger, 2009 ; McDonald et al., 2009 ; Nelson et al., 2011 ; Odom et al., 2021 ; Rice & Bass, 2009 ; Salas et al., 2018 ; Staniewicz et al., 2023 ; Stoeger et al., 2014 ; Sueur et al., 2011 ; Teixeira et al., 2022 ; Thode et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%